Textbook of Microbiology for Dental Students - Kumar, Surinder (New Delhi : Jaypee, 2013)
The book is divided into eight sections, based on the major disciplines included within syllabus of dental microbiology that is general bacteriology, immunology, systemic bacteriology, virology, medical mycology, medical parasitology, oral microbiology and clinical microbiology. In general bacteriology, systemic bacteriology, virology, medical parasitology and medical mycology sections are dealt with history, morphology, cultural characteristics, resistance, biochemical reaction, pathogenicity, clinical features, laboratory diagnosis and treatments. The oral microbiology section deals with different diseases or infection caused by various organisms in mouth with their symptoms, clinical features, diagnosis and treatment. The clinical microbiology section discusses about the various antibiotic sensitivity tests used in detecting antimicrobial compounds to treat the different infective syndromes. The immunology part deals with different types of immunity, immune responses, antigen-antibody reaction with its structure and function, hypersensitivity reaction, autoimmunity and different grafting methods.
Keywords: Microbiology; Microbiology and Immunology